Hubungan Self Efficacy Academic Dengan Social Loafing Pada Kelompok Belajar Mahasiswa - Hatiti, Kasih; Wahyuni, Citra; Maharani, Laila (ANFUSINA: Journal of Psychology, 2021)
Group learning methods during online learning are still applied with the aim of making it easier to do the tasks given. However, there are negative effects that arise from completing tasks in groups, one of which is the tendency of group members' behavior to reduce effort or also known as social loafing behavior. One way to minimize social loafing behavior is to increase academic self-efficacy in each individual. This study aims to determine the relationship between academic self-efficacy and social loafing in student study groups.The population in this study were students of the Islamic Study Program of UIN Raden Intan Lampung batch 2019 which consisted of five classes with a total of 154 students. The researcher used a quantitative research method with a sampling technique in the form of cluster random sampling and obtained a sample of 62 students from the population of class D and E. The data collection technique used the academic self-efficacy scale (α= 0.900) and the social loafing scale (α= 0.859). The data analysis technique used in this study is a correlation analysis technique with the help of the JASP 0.14.1.0 program. The results showed the value of r = -0.693 with a significance of p < 0.001, which means that there is a negative and significant relationship between academic self-efficacy and social loafing. The results also show that academic self-efficacy contributes 48% effectively to social loafing.Keywords: Social loafing, Academic Self efficacy, Students